Identity and motivation of adolescent student-athletes in school and elite sport: an investigation of the relationship within- and cross-domains - Maike Niehues; Lara Wille-Rex; Jeffrey Sallen; Jeffrey Sallen (Frontiers in Sports and Active Living)
IntroductionPrevious studies have highlighted the effects of motivation and identity on dual careers (DC) separately.MethodsThe present study investigated the mutual relationship among 495 student-athletes (mean age = 17.0, males = 56.6%) in upper secondary school. The Student Identity Measurement Scale (SIMS), Academic Identity Measurement Scale (AIMS), and Student-Athletes’ Academic and Athletic Motivation Scale (SAAMS) were used in a cross-sectional design.ResultsFindings revealed that student-athletes expressed higher identity than motivation within each domain. Athletic identification and motivation were stronger than those for academics. Correlation models revealed strong relations between identity and motivation within a domain, but not across domains. Gender differences emerged, with female student-athletes reporting higher academic identity and motivation compared to males.DiscussionThe study supports the notion that balancing both academia and sports is vital to prevent identity foreclosure and enhance a successful DC. Additionally, the need for individualised support and talent identification strategies for student-athletes is emphasised.